A figura feminina em Lídia Jorge: dominação, sacralidade, resistência - MENEGUNDES, Andréia Mendonça (2022)
The path of women in society is marked by a long in search of their emancipation and affirmation. Contemporaneity has seen some advances that have provided women with the possibility of overcoming some barriers who prevent such achievements. One of the ways to achieve the mechanisms who sustain the domination and opression of women over time. This work aims to investigate the representation of the female figure in the short story production by contemporary Portuguese author Lídia Jorge. In this perspective, we will analyze the tales “ Marido” and “ As três mulheres sagradas”, included in the literaries works Marido e outros contos (1997) and O belo adormecido (2004), respectively. The choice of these narratives is justifield because both presente female characters that give rise to a reflection on their conditions in na environment of domination and oppression, marked by referencer to sacred symbols, in which resistance presentes itself as necessary. With a qualitative and bibliographical basis, having as theoretical support Maria Leonor Carvalhão Buescu, Giorgio Agamben, Michel Foucault, Maria Graciete Besse, Pierre Boudieu, this research seeks to identify the stylistic resources used in the representation of the female figure in the analyzed tales. Therefore, it aims to demonstrate that the tales ́s production of Lídia Jorge is a field of ficction of representation of the condition feminine in contemporary times.